Greco-Roman associations: texts, translations, and commentary : Attica, Central Greece, Macedonia, Thrace - Kloppenborg, John S. (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2011)
Bibliographical Note; Sigla; Abbreviations; Calendars; Glossary; Maps; Introduction; ATTICA; CENTRAL GREECE; MACEDONIA; THRACE; Bibliography; Indexes; Concordance of Inscriptions